Toward Soluble 5,10-Diheterotruxenes: Synthesis and Reactivity of 5,10-Dioxatruxenes, 5,10-Dithiatruxenes, and 5,10-Diazatruxenes - Górski, Krzysztof (J Org Chem, 2020)
[Image: see text] The following work presents three general approaches allowing, for the first time, the synthesis of 5,10-diheterotruxene derivatives containing two identical heteroatoms, namely, oxygen OOC, nitrogen NNC, or sulfur SSC. Two of described pathways involve the photocyclization of the corresponding triene 2 as a key step leading to a heptacyclic aromatic system. The third approach is based on the acidic condensation between ninhydrin 14 and benzo[b]heteroole 15. Typical functionalizations of the 5,10-diheterotruxene core have also been presented. In addition, the article discusses the advantages and limitations of the three suggested paths for receiving specific 5,10-diheterotruxene derivatives because the universal method suitable for obtaining molecules with any type of heteroatoms is not known so far.